PENERAPAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS, MIKRO, KECIL, DAN MENENGAH (SAK EMKM) PADA UMKM PUFFY PATISSERIE - Ardiani, Dewa Ayu Putu Yulia; Nopiyani, Putu Eka (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
The main objective of this research is to find out whether Puffy Patisserie MSMEs use Entity, Micro, Small and Medium Financial Accounting Standards (SAK EMKM) in their financial report preparation procedures. The aim of this research is to create financial reports using the SAK EMKM framework, with a special focus on Puffy Patisserie MSMEs. The research materials used consist of a combination of qualitative and quantitative sources. The first source consists of interview data, and the second source is obtained from the financial records of MSME Puffy Patisserie. Based on the research results, the Puffy Patisserie MSME report is currently still in the form of a basic report, because the owner only documents income and expenses. (2) Due to the owner's lack of knowledge about how to prepare financial reports in line with SAK Entities, Micro, Small and Medium Enterprises (SAK EMKM), the report was not implemented. The Financial Position Report, Profit and Loss Report and Notes to the Financial Statements are financial reports that have been prepared in accordance with SAK EMKM for Puffy Patisserie MSMEs for the quarterly period January to April 2024.